Pengaruh Pemberian Teknik Relaksasi Otot Progresif terhadap Tingkat Stress pada Mahasiswa Ners Angkatan XI Selama Pandemi Covid-19 - Nurhaziza Hamsul; Munir, Nur Wahyuni; Taqiyah, Yusrah (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Stress in learning is a feeling faced by a person when there are pressures on him. The pressures in question are related to learning and school activities, such as the grace period of the task, on the eve of exams and thesis. The purpose of the study was to find out if there was any effect of providing progressive muscle relaxation techniques on students' stress levels during the covid-19 pandemic at the Muslim University of Indonesia. This type of research is a type of quantitative research. The research design used is a pre-experimental method with the One Group Pretest-Posttest Design approach. The determination of samples was done by purposive sampling technique with a large sample of 52 respondents. The comparison test is conducted using a paired t-test sample. The results of this study showed that before being given progressive muscle relaxation techniques to 52 students, stress was in the mild category of 35 students, while as many as 17 students while after being given progressive muscle relaxation techniques to 52 students obtained stress levels all students were in the normal category as many as 52 students. It can be concluded that there is an influence between progressive muscle relaxation techniques on stress levels with a significance value of 0.000 < 0.05, which is then expected to be more research on stress in students during the covid-19 pandemic so that more references, further research needs to be done with other methods and more samples in order to get more accurate results, because covid-19 causes the process of providing proresive muscle relaxation techniques that are It should be more effective face-to-face but because it is still a pandemic so researchers have to provide action online and only a small percentage of respondents can come face to face for the provision of progressive muscle relaxation techniques.